The Effects of Different Feed Enrichments on Survivorship and Growth of Early Juvenile Longsnout Seahorse, Hippocampus reidi. Issue 3 (9th June 2013) - Pham, Nancy Kim; Lin, Junda
Abstract Culturing the longsnout seahorse, Hippocampus reidi, remains challenging because unlike most cultured seahorse species, Artemia is not an optimal first feed. Ideally, more nutritious live feeds such as wild plankton or copepods should be used, but are not always readily available. Therefore, facilities commonly utilize enriched rotifers. Numerous feed enrichment products exist, including Dan's Feed Artemia Enrichment®, (Dan's Feed) which is a blend of commercially available enrichment products. The aim of this study was to assess the survivorship, growth, and condition factor (CF) of 0–28 DPR (days post release) H. reidi fed with rotifers and Artemia enriched with Dan's Feed. This enrichment was evaluated against (1) rotifers and Artemia enriched with live alga (Isochrysis galbana), and (2) wild plankton and Artemia enriched with Dan's Feed. At 28 DPR, in terms of survivorship and growth, seahorses fed with rotifers and Artemia enriched with Dan's Feed had a lower CF and outperformed those fed rotifers and Artemia enriched with I. galbana. Seahorses fed with rotifers and Artemia enriched with Dan's Feed performed on par with those fed with wild plankton and Artemia with no significant difference in CF. These findings demonstrated that the culture of H. reidi may be feasible with rotifers and Artemia enriched with Dan's Feed.